The Reinterpretation of the Harrowing of Hell in the Centro Aletti’s Liturgical Mosaics - Ruiz de Loizaga Martín, María (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2019)
The Centro Aletti’s mosaic programs are of liturgical nature and reflect the merger of tradition and contemporaneity. Byzantine art is among the iconographic sources emerging from tradition. The analysis of icon history reveals its profound meaning and the motivations for its presence in these mosaics. In this article, the reappearance of byzantine iconography and the church fathers as sources of tradition in the works of the centro aletti is analyzed emphasizing the reinterpretation proposed by marko ivan rupnik, its director, on the harrowing of hell.